Influence of parental participation in school management on academic performance in Catholic-owned schools - Munya, Rebecca Mwonjiru; Ibuathu, Charles Njati; Gathuru, Gitari (African Journal of Science, Technology and Social Sciences, 2025)
Parental involvement is a recognised factor in students’ academic success, yet its influence through school governance structures in faith-based institutions remains under-investigated in Kenya. This study explores the relationship between parental participation in school management and academic performance in Catholic-owned primary and secondary schools in Isiolo County. The primary objective was to determine how parents’ involvement in school governance, through roles in Boards of Management (BOM), Parents Associations (PA), and school management committees, influences students’ performance in national examinations. A descriptive survey design was adopted, targeting a population of 1,745 stakeholders. A sample of 224 participants was selected, comprising BOM and PA members, school managers, students, head teachers, and an education secretary. Although purposive sampling was employed due to the study’s focus on Catholic-owned schools, the concentration of such institutions in the area supported representativeness. Data collection involved structured questionnaires, interviews, observations, and document analysis of KCPE and KCSE results from 2008–2012. Academic performance was analyzed in relation to school-level governance practices, while efforts were made to account for confounding variables such as school size, location, and resource availability. Findings revealed that while all schools had active, only 25% of parents participated in funding or strategic initiatives. Most PA meetings focused on discipline, motivation, and academic issues, yet participation in decision-making on school projects and resource allocation was minimal. Schools with structured parental engagement reported improved monitoring of academic progress and communication practices. However, challenges such as student indiscipline (53.33%) and parental apathy (26.67%) hindered broader involvement. The study found a modest correlation between parental participation in school governance and improved academic oversight, though causality could not be definitively established due to the multifactorial nature of academic achievement. The study concludes that while parental involvement exists, its impact is constrained by limited roles in strategic planning and resource mobilisation. It recommends the development of inclusive frameworks and policies that empower parents as active contributors to governance in faith-based schools. These findings offer context-specific insights into participatory governance and its potential in enhancing educational outcomes in marginalised settings.